جماليات النظرية النسوية عند جوليا كريستيفا: دراسة فى إتيقا الأنثوى - بكاي، محمد (الهيئة المصرية العامة للكتاب, 2018)
The feminism's theorist Julia Kristeva presented new and different perceptions of female situations; where the psychological experiences are taken seriously by opening new ethical, social and political pages. Strongly pushed the wheel of difference’s ethics or inter subjectivity in the circles of contemporary feminist ethics. It is a vital dimension for the vision of a wise rationality based on universal concepts of the individual and his sensual identity, complementing rational moral projects by adding neglected or marginalized aspects, most of which relate to sensuality and intimacy; Through a journey of revelation to unprecedented efforts in criticism and psychoanalysis, Kristeva deviates from outdated and established perceptions of language and identity and seeks an analytical way to blow it up by moving stagnant pond water or lifting the veil from that silent zone. Where the human identity lives her revolutions and disobedience in the form of tensions and interactions, which is contrary to the idea of the organization and the formalisme that established the structuralism.
قدمت المنظرة النسوية جوليا كريستيفا تصورات جديدة ومغايرة لحالات الأنثى؛ تؤخذ فيها التجارب النفسية على محمل الجد، عبر فتح صفحات جديدة أخلاقية واجتماعية وسياسية. دفعت بقوة عجلة أخلاقيات الاختلاف أو التذواتية في دوائر الأخلاق النسوية المعاصرة. وهو بعد حيوي لرؤية إتيقية حكيمة تتكئ قاعدتها على مفاهيم شاملة للفرد وهويته الحسية استكمالا للمشاريع الأخلاقية العقلانية بإضافة جوانب مهملة أو مهمشة تتصل أغلبها بالحسي والحميمي. عبر رحلة كشفية لجهود غير مسبوقة في النقد والتحليل النفسي، تجتث كريستيفا التصورات البالية والراسخة للغة والذات، وتبحث عن طريقة تحليلية لتفجيرها، بإعادة تحريك مياه البركة الراكدة أو رفع الحجب عن تلك المنطقة الصامتة، حيث تعيش النفس الإنسانية ثوراتها وعصيانها في شكل توترات وتجاذبات، وهو ما يتنافر مع فكرة التنظيم والنسق التي أسست لها البنيوية.
Keywords: النقد الأدبى -- النقد النسوى -- النظرية النسوية -- كريستيفا، جوليا -- إتيقا الأنثوى -- السيميائية -- ما بعد البنيوية